Learning critical thinking and critical thinking disposition among year 3 diploma nursing students of UMS - Norkiah Arsat; Segaran Ramodran; Farah RazeeraVidy; Nor Hafiqah Mohd Taib; Dylela Lee Geem (Malaysian Journal of Medicine and Health Sciences, 2020)
Nursing students have been educated with critical thinking in client care. However, nursing students are often considered to be lacking in critical thinking especially during their clinical experience. This is likely due to lack of knowledge of critical thinking as the opportunities for learning critical thinking (LCT) are limited and less en¬couraged to use critical thinking during the teaching and learning process. Therefore, it contributes to poor learning outcomes.The aim of this study was to identify level of LCT and critical thinking disposition (CTD) among diploma nursing student of UMS. Methods: A cross sectional survey design using purposive sampling methods. Sixty (60) of 66 year3 nursing students completed aCTD Inventory for Chinese Medical College Students (CTDI-M) by Wang et al (2019) and The LCT Inventory (LCTI) and the Teaching Critical Thinking Inventory (TCTI) developed by van Zyl, M.A., Bays, C.L., & Gilchrist, C. (2013).Approval to conduct study obtained from Dean of faculty of Medicine and Health Sciences, UMS. Results: The data were analyzed through descriptive method using SPSS for window 21.0. Total score for CTD ranging from a low (M= 1.5) to a high (M=5.00), Mean value 3.86, (SD +/- .572). Total high-level CDT 58(96.7%). Total LCT scores ranging from a low (M=2.00) to high (M=5.00) and Mean value 4.02, (SD +/- .711). Total high level LCT 54(90%). The two subscale categories were analyzed for perceived LCT. Respondents reported significantly high level of both instructor helped in LCT 51(85%) and 56 (93.3%) provides support and encourage¬ment in LCT, mean value 4.19 (SD+/-.713). Conclusion: The level of CTD and LCT was high, shows that nursing students perceive themselves as having a high level of critical thinking motivation, instructor providing guidance to assist and encourage to learn using critical thinking.